Pengaruh Keputusan Investasi Terhadap Finansial Freedom Pada Pelaku UMKM di Madura - Fariyana Kusumawati; Nurul Kompyurini (Jurnal Penelitian Teori & Terapan Akuntansi (PETA), 2025)
This study analyzes the influence of investment decisions based on the effectiveness of financial management, investment experience, and gender factors on the financial freedom of micro, small, and medium enterprises (MSMEs). The objective of this research is to evaluate how effective financial management, investment experience, and gender impact the financial freedom of MSME actors. This research employs a quantitative approach. The population consists of MSME actors located in the Madura region. Samples were taken using convenience sampling methods, and data were collected through the distribution of questionnaires. Data analysis was conducted using multiple linear regression techniques. The results indicate that investment decisions based on effective financial management, experience, and gender have an influence on financial freedom, while investment decisions based on gender do not demonstrate a significant effect on financial freedom